STABILITY ANALYSIS OF OPRIT ON THE SEI TUAK BRIDGE WITH REINFORCEMENT MODULAR SYSTEM DISTRICT PASER, TANAH GROGOT - Markawie Markawie (INFO-TEKNIK, 2011)
Height of oprit on  Sei Tuak Bridge reaches 3,5 m. Oprit made by  new system, modular wall. Advantages of modular system are : construcability, has a positive aspect of the schedule, the number of field workers and office project are few, aspect of quality dan productivity, testing. Modular walls is choosed  to increase aesthetics value. Modular wall are used on sand. However, in Sei Tuak Bridge modular wall built on clay. The purpose of analysis are analyzed stability oprit on the Sei Tuak Bridge. The result of analysis shows : soil active pressure at the first segment is 0.193 ton detained by deadmen is 0.235 ton, at the second segment is 0.2895 ton detained by deadmen is 1.873 ton, at the third segment is 0.2895 ton detained by deadmen is 2.474 ton, at the fourth segment is 0.355 ton detained by deadmen  is 3.075 ton, and the fifth segment is 0.732 ton detained by deadmen is 3.675 ton. Deadmen is located at a distance 3.5 m. Its longer than failure area at 2.103 m. Safety factor of  tierod at the first segment is 22.854, at the second segment 15.236, at the third 15.236, at the fourth segment is 12.425, and at the fifth segment is 6.026. Safety factor of bearing capacity is 1.122. And safety factor of this modular wall  stability is 2.724.